Neutron flux distributions in the Large Helical Device torus hall evaluated by an imaging plate technique in the first campaign of the deuterium plasma experiment. (17th September 2019) - Kobayashi, Makoto; Tanaka, Tomoyo; Nishitani, Takeo; Ogawa, Kunihiro; Isobe, Mitsutaka; Motojima, Gen; Kato, Akemi; Yoshihashi, Sachiko; Osakabe, Masaki
Abstract: The global flux distributions for thermal, epithermal and fast neutrons in the torus hall of large fusion devices were experimentally evaluated for the first time in the Large Helical Device (LHD) using the activation foil method measured by the imaging plate and high-purity germanium detector. It turned out that the thermal neutrons were effectively absorbed by borated polyethylene blocks placed beneath the LHD. This should reduce the radioactivity of the floor and would be beneficial in maintaining a good environment for radiation workers. Uniform distributions of epithermal and fast neutrons were observed near the LHD. In particular, the significant decrease in fast neutron flux with increasing distance from the LHD, due to the fast energy loss of fast neutrons, was observed. The neutron flux distribution measurement, with rough energy discrimination based on the threshold energy of the neutron activation foil, allows us to estimate the spatial radiation dose rate, as well as the radioactivity in components in the torus hall. The prediction of the radioactivity in the concrete floor indicated that radioactive isotope 55 Fe will be a dominant source of radioactivity in the concrete after the nine-year deuterium experiment campaign finishes.